Students’ Argumentative Ability in the Graduate Thesis Introductions - Annisa Annisa (Institut Agama Islam Negeri Palopo, 2023)
The research aimed to explore the students’ argumentative ability in their thesis introduction and to explore the most difficult moves for students in their thesis introduction. Students’ argumentative ability refers to the way students write their thesis introductions by following swales’ pattern (1990). Swales’ Pattern consist of three moves, establishing a research territory, establishing a niche, and occupying the niche.This research used a Descriptive Quantitative Method. The sample of this research were graduate students thesis from the Graduate Program of English Language Education at Muhammadiyah University of Makassar who completed their studies in 2021. The total sample was sixteen graduate students thesis. The procedure of this research was collected by analysing the students’ thesis introduction by using a rubric.The results of research found that 1) Students’ argumentative ability in the graduate thesis introductions was good which the students wrote their introduction by claiming the importance of the research (move 1 step 1), reviewing items of previous research (move 1 step 2), indicating a gap (move 2 step 2) and outlining the purposes (move 3 step 1). 2) The most difficult moves for students were move one step two (reviewing items of previous research), and move two step one (indicating a gap). It was identified based on the lowest score got by the students in each move. Therefore, it can be concluded that in writing thesis introductions, the students from Graduate Program of English Language Education at Muhammadiyah University of Makassar who completed their studies in 2021 followed Swales’ Pattern (1990).